Missverständnisse und die Grenzen des Verstehens: zum Verstehen diesseits und jenseits der Grenzen historischer Vernunft - Stoellger, Philipp (Zeitschrift für Theologie und Kirche, 2009)
Biblical texts make demands which the reader cannot refrain from answering. In giving an answer, the reader should dare to say more than the text has already said and to take responsibility for this. This biblical demand forces us to understand by ourselves and does not offer the possibility of referring to something that is already understood. To understand a biblical text, one must therefore take the risk of misunderstanding. In view of this precarious freedom, the author shows that hermeneutical research is necessary in order to avoid accidents in understanding. We first see a text, then we read it and finally understand it by creating a »text world«. Thus we can misunderstand a text if we don't see or read it correctly or if we miss the essence of the text. Any research on misunderstanding texts would have to deal with the relationship between the reader's own understanding and that which is not the reader's own. Understanding is not only what we understand, nor is it only understanding that which is foreign to us in a text, it is always both.